The Effect Of Positive Affirmation Therapy And Ablution Therapy Before Bed On The Level Of Insomnia In The Elderly At PSTW Budi Luhur - Andini, Febri Tri; Resqitha Ekaputri, Kintan; Oktaria, Rina; Nasution, Riska Amalya; Sari, Putri Irwanti (Jurnal Ilmu-Ilmu Kesehatan, 2025)
Insomnia is an inability to sleep complaints simultaneously increasing due to increasing age. The purpose of this research is to know the influence of positive affirmation and ablution therapy before going to bed in elderly at PSTW Budi Luhur. Research design used in the study is pre experiment with the approach of one group pretest posttest. Sampling techniques with non-probability sampling methods with purposive sampling retrieved 15 samples of respondents. Method of data collection using the questionnaire KSPBJ Insomnia Rating Scale as for the analysis of data using t tests. Based on statistical t test obtained p value = 0.005 less than α = 0.05 ( p value= 0.005 < α = 0.05). It indicates Ho is rejected and H1 accepted, it means that there was influence of positive affirmation and ablution therapy before going to bed in the level of insomnia in elderly of PSTW Warga Tama, Inderalaya. The results of this research suggest that the elderly can overcome insomnia by applying positive affirmations and ablution therapy before going to bed as a reference in the elderly health improvement efforts especially the elderly who experience insomnia. Keywords : Positive affirmation, ablution therapy, insomnia, elderly